Labor Market Analysis Using Big Data : The Case of a Pakistani Online Job Portal - Matsuda, Norihiko (World Bank, Washington, DC, 2019)
Facing a youth bulge—a large influx of a young labor force—the Pakistani economy needs to create more jobs by taking advantage of this relatively well-educated young labor force. Yet, the educated young labor force suffers a higher unemployment rate, and there is a concern that the current education and training system in the country does not respond to skill demands in the private sector. This paper provides new descriptives about labor markets, particularly skill demand and supply, by using online job portal data. The paper finds that although there is an excess supply of highly educated workers, certain industries, such as information and communications technology, lack workers who have specialized skills and experience. The analysis also finds that the exact match of qualifications and skills is important for employers. Job applicants who are underqualified or overqualified for job posts are less likely to be shortlisted than those whose qualifications exactly match job requirements.